Whole-genome sequencing of penicillium georgiense, a member of the family trichocomaceae isolated from harumanis mango (Mangifera Indica L.) - Hajar Fauzan, Ahmad; M. S. I., Sahran; Teoh, Jasmine Wen Yi; Siti Khadijah, Kiram; Jeyakirtana, Jayabalan; Muhammad Ikhmal, Rosali; Siti Munirah, Musa (Penerbit Universiti Malaysia Pahang, 2023)
Microbial communities are present in various environments, influencing their hosts through both advantageous and pathogenic interactions. The advent of next-generation sequencing technologies has enabled more comprehensive exploration of these complex communities. Penicillium georgiense (P. georgiense), a known pathogenic fungus, has been shown to cause significant spoilage through rapid colonization enabled by spore production, particularly affecting long-term storage. Contamination by Penicillium species poses risks to crops health, emphasizing the need for effective post-harvest management. In this study, Harumanis mango, widely consumed in Asia, especially in Malaysia, was selected as the model host. A single colony of P. georgiense was isolated, and their genomic DNA was extracted. The genome of the P. georgiense H_A strain was sequenced using the Illumina NovaSeq 6000 platform with short-read technology, revealing a genome size of 18,324,307 base pairs and a GC content of 46.2%. BUSCO analysis indicated 98% genome completeness, with high similarity to the P. georgiense SRG7 isolate. The annotated genome has been deposited in the NCBI GenBank database for accessibility. This study provides important genomic insights into P. georgiense, advancing our understanding of its pathogenic mechanisms and offering valuable data for improved post-harvest management of Harumanis mango.